Taxing the Family Work: Aid for Affluent Husband Care - McCluskey, Martha T. (Columbia Journal of Gender and Law, 2011)
The income of the classic breadwinner married to a homemaker receives a tax advantage under federal income tax law. The conventional wisdom holds that any resulting inequities to unmarried persons or dual-earning marriages cannot be corrected without producing similarly problematic inequities. This Article challenges that dilemma by analyzing the inequity of the marital tax system from a new perspective. This Article argues that the perceived “bonus” for breadwinner-homemaker marriages is best understood as an implicit policy of “aid for affluent husband care.” Recent tax reforms (up for renewal in 2010) that partly reduced the “marriage penalty” for some dual-earning couples are inequitable not simply because these reforms exclude upper-income and lower-income marriages while penalizing single persons. More fundamentally, this Article shows how these tax reforms increase a regressive system of support for the family caretaking labor on which income earning depends. This Article aims to show how a change to individualized, more progressive rates could more equitably treat income earning and informal caretaking labor regardless of family status.